The Role of Customer Satisfaction Mediates The Effect of Service Quality on Customer Loyalty in Online Transportation - Kadek Andika Saputra; Gusti Ayu Sugiati (Jurnal Ekonomi dan Bisnis Jagaditha, 2023)
The purpose of this research was to analyze the role of customer satisfaction in mediating service quality and customer loyalty for Grab customers in Denpasar. This research is a type of associative study. The research population is customers of Grab bike service in Denpasar city and sample determination in this study uses probabilistic sampling by random sampling. The sample of this study is 100 customers of online motorcycle taxi users. The primary data source is the respondents who directly respond to the survey variable being tested. Data collection used in study is by distributing questionnaires to 100 respondents and data analysis technique used is Partial Least Square (PLS). The research results show that the variable customer satisfaction is a good mediator between service quality and customer loyalty. The existing relationship is a positive relationship where as the service quality of Grab-Bike in Denpasar improves, so does customer satisfaction, which in turn increases customer loyalty.